How do Coaches` Attitudes Change When Exposed to a Sport Psychology Workshop? - Zakrajsek, R. A.; Zizzi, S. J. (Journal of Coaching Education, 2008)
This study examined: (1) coaches` attitudes and readiness to use sport psychology (SP) services immediately following a SP workshop; and (2) the impact of an educational intervention on coaches` attitudes and usage patterns during a one-month follow-up. Ninety swim coaches participated in the SP workshop and a total of 53 swim coaches completed the one-month follow-up. The majority of the sample coached at the high school or age group level. Data provided some evidence for the impact of a SP workshop on stage of change, with approximately 13% of coaches moving from precontemplation to contemplation. Two-way mixed ANOVAs did not reveal significant interactions (group x time) and main effects for time found that coaches` personal openness, behavioral control, self-efficacy, and intentions increased while perceived barriers decreased immediately post-workshop. Furthermore, changes in coaches` perceived barriers, behavioral control, and self-efficacy were maintained at the one-month follow-up while personal openness and intentions returned close to baseline. Lastly, no differences were found between the stage-matched and control group with regard to behavioral SP usage patterns (e.g., contacting a SP consultant, seeking out more information about SP). However, approximately 40% of coaches accessed the website during the four-week follow-up. The appropriateness of the transtheoretical model of behavior change applied to SP service use with coaches will be discussed.